Profissionalização e governança na empresa familiar: novos e velhos arranjos familiares e organizacionais - Suélen Rodrigues Miranda (2014)
The family company has peculiar ways of management, that end up printing to the business behavioral characteristics related to the vicissitudes of the relationship between the family and the business. With that , often , the separation between ownership and management is difficult, which can lead to equity issues and problems of demarcation between the spheres of activity of family and business, with impacts on the performance and even the survival of companies. In an attempt to understand the inherent complexity of these developments and contribute to the field of research in the area, the present study was developed with the aim of analyzing the evolution of professionalization mechanisms and governance in two Brazilian companies descent. The theoretical basis used for this study has its foundations on three themes: Family Business, Professionalization in the family business and Governance in the family business. Regarding the methodology undertaken for this research, we chose a qualitative research approach. As a research method, two case studies were conducted - in Randon S/A Implementos e Participações (RS) and Companhia de Fiação e Tecidos Cedro e Cachoeira (MG). Each case is designed and analyzed specifically and subsequently held the inter cases analysis, from the themes and categories of analysis established for the study. As instruments of data collection interviews and documentary research were conducted. The subjects of the research were interviewed family members who work or have worked in the company, directors, corporate officers and professional officers. As a technique for data analysis, content analysis was used. The results showed that, due to the different contexts and historical companies surveyed, they made different choices with regard to the mechanisms of governance and family governance and processes of professionalization and succession. These arrangements take into account the need to accommodate political issues and power in the family and company. It is evident that some practices need to move quite yet, in order to meet not only the family interests but also the interests of other shareholders and so-called good governance practices, as both companies integrate the different levels of governance BOVESPA.